2011
DOI: 10.1097/pec.0b013e31823aff6d
|View full text |Cite
|
Sign up to set email alerts
|

Safety of High-Concentration Nitrous Oxide by Nasal Mask for Pediatric Procedural Sedation

Abstract: Nitrous oxide can be safely administered at up to 70% concentration by nasal mask for pediatric procedural sedation, particularly for short (<15 minutes) procedures. Nitrous oxide seems safe for children of all ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 32 publications
4
48
0
4
Order By: Relevance
“…There have been many studies illustrating the safe use of ketamine and N 2 O for procedural sedation by ED physicians and intensivists. [3][4][5][6][7] This is the fi rst study demonstrating the safe and effective use of ketamine and N 2 O by PH. It is important to note that a comprehensive sedation training program with anesthesia oversight and close collaboration with anesthesiologists is a key element of the PH sedation program at SLCH.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There have been many studies illustrating the safe use of ketamine and N 2 O for procedural sedation by ED physicians and intensivists. [3][4][5][6][7] This is the fi rst study demonstrating the safe and effective use of ketamine and N 2 O by PH. It is important to note that a comprehensive sedation training program with anesthesia oversight and close collaboration with anesthesiologists is a key element of the PH sedation program at SLCH.…”
Section: Discussionmentioning
confidence: 96%
“…2 Several studies have demonstrated the safety of procedural sedation using ketamine and nitrous oxide (N 2 O) by emergency physicians and intensivists. [3][4][5][6][7] Pediatric intensivists and emergency physicians have been the primary nonanesthesiologist sedation providers because they have the greatest experience managing the pediatric airway in patients in the emergency department (ED) and ICU. However, pediatric hospitalists (PH) are increasingly providing sedation for various painful procedures and for radiologic imaging of children across the nation.…”
mentioning
confidence: 99%
“…Such experiences not only affect the outcome of the procedure, but also future procedures . Although nitrous oxide has been used as a safe and effective analgesic for children undergoing many types of minor painful procedures, its effectiveness is not widely described, nor is its use common in pediatric oncology patients undergoing repeated lumbar punctures on an outpatient basis.…”
Section: Introductionmentioning
confidence: 99%
“…The nausea/vomiting with N 2 O is dose-and duration-dependent (>10-15 minutes after administration). [24][25][26] Some authors have reported delayed vomiting with N 2 O, and caregivers should be informed that this can occur post-discharge. 25 Vasovagal syncope was described in 1 case report included in this review with IN dexmedetomidine.…”
Section: Practical Considerationsmentioning
confidence: 99%